2001
DOI: 10.1021/la010405c
|View full text |Cite
|
Sign up to set email alerts
|

Protein-Induced Changes in Poly(ethylene glycol) Brushes:  Molecular Weight and Temperature Dependence

Abstract: Terminally grafted chains of poly(ethylene glycol) (PEG) and oligo(ethylene glycol) reduce protein adsorption and cell adhesion on material surfaces. However, previous studies showed that protein−PEG adhesion is induced by the application of pressure. Because polymer behavior can vary with the molecular weight, in this study we directly measured the forces between streptavidin and end-grafted monolayers of PEG of different molecular weights and at grafting densities. The results of these measurements show that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
164
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(180 citation statements)
references
References 78 publications
16
164
0
Order By: Relevance
“…It has furthermore been shown that PEO can exist in a protein-repulsive, polar, helical or random structure, and a protein-attractive, apolar, all-trans structure (Harder et al, 1998;Currie et al, 2003). The work of Efremova et al (2001) showed that changing circumstances, such as temperature or compressive load, can change PEO from a protein-repellent to a protein-attractive state. Conclusively, one can imagine that the hydrophobic surface of a microorganism can induce this attractive state, thus explaining the smaller reductions in adhesion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has furthermore been shown that PEO can exist in a protein-repulsive, polar, helical or random structure, and a protein-attractive, apolar, all-trans structure (Harder et al, 1998;Currie et al, 2003). The work of Efremova et al (2001) showed that changing circumstances, such as temperature or compressive load, can change PEO from a protein-repellent to a protein-attractive state. Conclusively, one can imagine that the hydrophobic surface of a microorganism can induce this attractive state, thus explaining the smaller reductions in adhesion.…”
Section: Discussionmentioning
confidence: 99%
“…This model assumes ideal chains that interpenetrate freely and exhibit no correlations and has been shown to give a fair prediction of PEObrush length in water (Efremova et al, 2001).…”
Section: Methodsmentioning
confidence: 99%
“…In the case of PEG's of 5000 to 6000 MW this may involve polymer layer thicknesses of 40 to 100 Å (29). Naturally there are conditions (raised salt concentration, temperature and pressure) where the polymer can be induced to interact more favourably with the surface and affect its surface conformation as well as protein adsorption.…”
Section: Modelmentioning
confidence: 99%
“…PEG molecules might assume pancake, mushroom, or brush conformations depending upon the distance between the covalently linked molecules and the properties of the surface. 32,33 Based upon calculations for the expected structure, the number of PEG-biotin molecules per EC observed in this study would occupy 87% or 6% of the cell surface if the PEG molecules were in the mushroom or brush conformation, respectively. 32,33 A potential benefit to using the approach of this study would be the ability to target pharmaceuticals or vectors to specific sites within the vasculature labeled with PEG-biotin for therapeutic benefit.…”
Section: Discussionmentioning
confidence: 99%
“…32,33 Based upon calculations for the expected structure, the number of PEG-biotin molecules per EC observed in this study would occupy 87% or 6% of the cell surface if the PEG molecules were in the mushroom or brush conformation, respectively. 32,33 A potential benefit to using the approach of this study would be the ability to target pharmaceuticals or vectors to specific sites within the vasculature labeled with PEG-biotin for therapeutic benefit. Delivery of pharmaceutical agents to sites of vascular injury is another strategy to reduce acute platelet deposition and possibly inhibit intimal hyperplasia.…”
Section: Discussionmentioning
confidence: 99%